Peran Teknologi Budidaya Modern Dalam Meningkatkan Produktivitas Tanaman Padi (Oryza Sativa L.) - Feberkat Abdi Mosinema Waruwu; Diverman Gulo; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Rice (Oryza sativa L.) is a primary food commodity vital to achieving national food security in Indonesia. However, challenges to increasing rice productivity, such as land degradation, climate change, and limited human resources, pose significant obstacles. The application of modern cultivation technologies is a strategic solution to address these challenges. Innovations such as new superior varieties (VUB), precision irrigation, agricultural mechanization, the jajar legowo (sequence planting system), and digital-based technologies such as the Internet of Things (IoT) and drones have been proven to increase rice production efficiency and yields. System of Rice Intensification (SRI) technology, for example, has shown yield increases of up to 20–50% compared to conventional methods. Furthermore, mechanized harvesting and planting can reduce labor costs and accelerate production times. This study uses a literature review approach to identify the role and impact of modern cultivation technologies on rice productivity in Indonesia. The results indicate that synergy between technology, training, and policy support is essential for widespread and sustainable technology adoption. Thus, the use of modern cultivation technologies has significant potential to support food self-sufficiency and improve farmer welfare.